Acrylamide Induced Neurotoxicity in Workers - Yohanes Edwin Jonatan; Andreas Kresna (ILUNI MKK FKUI and PRODI MKK FKUI, 2022)
Background: Acrylamide (ACR) are used in many chemical and industrial process. They exposure to human pose some health risk, while some effects are proven, the causal relationship between ACR and neurotoxicity is still unclear, so we would like to look for some evidence regarding this issue. The search for evidence is also complemented with a seven-step occupational disease assessment in order to establish occupational disease diagnosis.Methods: Searching literature for the evidence-based has been conducted with a clinical question through “PICO” method. Then we continued the searching using electronic databases: “PubMed”, “Google Scholar”, and “Cochrane Library” search engine. The keyword is Acrylamide” “2-Propenamide; Ethylenecarboxamide” “Neurotoxic” combined with Boolean operation. The inclusion criteria are research in human, publication last ten years, and English full text article, while our exclusion criteria are duplicate or not relevant study.Results: From the three literatures obtained, we could obtain the description of neurotoxicity symptoms induced by acrylamide, the diagnosis and treatment, and also the mechanism how acrylamide could induce neurotoxicity in human.Conclusion: Acrylamide exposure in workers can cause neurotoxicity depend on the duration and concentration of exposure.